Análisis kaldoriano de la industria manufacturera risaraldense, 1980-2007 (2019)
Throughout the article, the authors present a performanceanalysis of the manufacturing industry in the department ofRisaralda for the period 1980-2007; for this, the theoreticalguide from the economist N. Kaldor is a contribution throughwhat is known in the literature as "Kaldor's three laws." Theseformalized set of dynamic relationships can be generatedbetween the productive sectors of the economy, the role ofsector productivities, and particularly the development of themanufacturing industry, which is considered as the growthengine of a country, from an endogenous approach. Specifically, it will be use the first two theoretical propositions;the first referring to the high correlation between the growth ofmanufacturing output and GDP growth; the second refers tothe existence of a positive and significant relationship betweenthe growth of productivity of the manufacturing industry andthe output growth rate. This relationship is also known as the"Verdoorn Law" (1949). Therefore, this article has the dual purpose of comparing thereality of the manufacturing department with the first twoKaldorians propositions, also, as to revive the theory ofendogenous growth and increasing returns in the line ofYoung, applied to the growth and development of the regionaleconomy.